The influence of academic values on academic engagement among Chinese college students: A serial mediation model - Jingyi Dong; Tiantian Yang; Zhixia Wei; Xiaoxia Gu; Yangshu Ru; Ling Hu (PLoS ONE, 2026)
This study investigated how academic values shape academic engagement among Chinese college students by examining the mediating roles of academic self-efficacy, autonomous motivation, and controlled motivation. Using a quantitative design with random sampling, valid data were collected from 1,110 students who completed four validated instruments: the College Students’ Academic Values Questionnaire, the Academic Self-Efficacy Scale, the Academic Motivation Questionnaire, and the Academic Engagement Scale. Structural equation modeling was used to test a serial mediation model. The findings revealed that academic self-efficacy, autonomous motivation, and controlled motivation mediated the relationship between academic values and academic engagement. Moreover, academic self-efficacy and both motivational types formed significant serial mediation pathways that explain how values influence engagement. Notably, the mediation pathways involving controlled motivation produced negative indirect effects, suggesting that controlled motivation may weaken students’ academic engagement.